ENRIQUE PEÑA NIETO’S EDUCATION REFORM IN THE WAITING ROOM - Wątróbka, Magdalena Małgorzata (The Copernicus Journal of Political Studies, 2018)
The analysis provided in this article aims to explain and disclose the processes that have influenced the education system in Mexico since the Aztec Empire, until the presidency of Enrique Peña Nieto. One of the issues presented in this paper is relation established by political party PRI (Partido Revolucionario Institucional) who rules Mexico for more than 70 years and institutions responsible for education, leading to centralization. The consequence of these processes is the attempt to introduce education reform by the government Enrique Peña Nieto. Without a doubt, the most important question asked in this article is „why education reform causes so many emotions among the teachers, especially members of the union and their associating organizations?”.